Construction Project Manager’s Emotional Intelligence and Team Effectiveness: The Mediating Role of Team Cohesion and the Moderating Effect of Time - Zhang, Qi; Hao, Shengyue (Frontiers in Psychology, 2022)
The emotional intelligence of a construction project manager plays an essential role in project management, and recent developments in teamwork have increased the need to explore better ways to utilize teams and achieve effectiveness in the construction sector. However, research that holds the team-level perspective in emotional intelligence studies is lacking, and the mechanism of the construction project manager’s emotional intelligence on team effectiveness remains unex-plored. This knowledge gap is addressed by developing a model that illuminates how construc-tion project manger’s emotional intelligence can affect team effectiveness via the mediation of team cohesion and the moderation of project team duration. A questionnaire survey was utilized to gather information from construction project teams across 156 leader-member dyads in the Chinese construction industry. The results reveal that construction project manager’s emotional intelligence is positively related to team effectiveness and the team cohesion mediates this cause and effect. Further, project team duration moderates the relationship between team cohesion and effectiveness. This study offers new insight into how project manager can better lead team mem-bers toward desired team outcomes from a team perspective and makes an explorative effort in investigating the “time” role in construction project management.